Recruiting for your Department: The Role of the Chair - Jennifer Dennis; Stephanie Boss; Mary Dzindolet; Lisa Huffman (Academic Chairpersons Conference Proceedings, 2018)
The chairs of an Education, Sports & Exercise Science, and Psychology Departments, and their former dean, share how they have been able to implement innovative recruitment strategies from an academic standpoint to increase enrollment in their departments and in the School of Graduate and Professional Studies.
Keywords: Recruitment; Enrollment; Innovation; Data; Alumni